Analysis User Satisfaction with the Shopee Application User Interface and User Experience Using the C4.5 Algorithm Among Digital Business Students Universitas Negeri Medan - Fitri, Anisa; Haryadi, Haryadi; Rahman, Haikal; Syah, Dedy Husrizal; Siregar, Zulkarnain (Economic: Journal Economic and Business, 2025)
This research aims to determine the level of user satisfaction with the user interface and user experience of the Shopee Application by classifying it using the C.4.5 algorithm. The research subjects used in this study are students of the Digital Business Study Program at Universitas Negeri Medan. This research uses a descriptive quantitative approach, with data collection through questionnaires designed using a Likert scale. The data obtained will then be analyzed using the C4.5 algorithm to produce a decision tree consisting of eight attributes used, namely strive for consistency, usability, offer information feedback, design dialogs to yield closure, prevent errors, permit easy reversal of action, keep user in control, and reduce short-term memory load. The result of the decision tree will form a rule or pattern that is easier to understand. From the data that has been collected, this research shows that the majority of user satisfaction levels fall under the class label category "SATISFIED," with the data divided into three classes: very satisfied, satisfied, and dissatisfied. In this study, the C4.5 algorithm was very capable of building a good classification model with an accuracy rate of 95%. This shows that the model is capable of classifying user satisfaction data very well.